2018
DOI: 10.1007/s00572-018-0839-7
|View full text |Cite
|
Sign up to set email alerts
|

Wetland plant species improve performance when inoculated with arbuscular mycorrhizal fungi: a meta-analysis of experimental pot studies

Abstract: The presence of arbuscular mycorrhizal fungi (AMF) in wetlands is widespread. Wetlands are transition ecosystems between aquatic and terrestrial systems, where shallow water stands or moves over the land surface. The presence of AMF in wetlands suggests that they are ecologically significant; however, their function is not yet clearly understood. With the aim of determining the overall magnitude and direction of AMF effect on wetland plants associated with them in pot assays, we conducted a meta-analysis of da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 111 publications
2
11
0
Order By: Relevance
“…Consistently with results presented here, AMF spores extracted from the rhizosphere soil of colonized native and exotic Fabaceae showed the dominance of Glomerales, but Archaeosporales and Diversisporales were also present (Tibbett et al 2008). In a recent meta-analysis, Ramírez-Viga et al (2018) concluded that AMF improve plant performance in wetlands through higher nutrient acquisition, photosynthetic activity, biomass generation, and mitigation of abiotic stress. However, understanding the functionality of AMF in M. pigra plants is a future task.…”
Section: Sequencesupporting
confidence: 89%
“…Consistently with results presented here, AMF spores extracted from the rhizosphere soil of colonized native and exotic Fabaceae showed the dominance of Glomerales, but Archaeosporales and Diversisporales were also present (Tibbett et al 2008). In a recent meta-analysis, Ramírez-Viga et al (2018) concluded that AMF improve plant performance in wetlands through higher nutrient acquisition, photosynthetic activity, biomass generation, and mitigation of abiotic stress. However, understanding the functionality of AMF in M. pigra plants is a future task.…”
Section: Sequencesupporting
confidence: 89%
“…Mixed‐effect models allow the specification of fixed effects and of random terms. To avoid the nonindependence of the data we included the study identifier (ID), the experiment ID nested within study ID and host ID as random terms in order to contemplate and control the random variation of several outcomes from a single study, treatment or host identity (Tuck et al ., 2014; Ramírez‐Viga et al ., 2018; Primieri et al ., 2022). Moderator levels with three or fewer outcomes (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The fungus then exchanges these nutrients for C compounds from the host plant [16][17][18]. Transfer of resources from a fungus to the host has been shown to be highly variable, and depend on factors including available soil nutrients [19,20], host species [21], host age [22], light availability [23][24][25][26][27], and even host sex [28]. Because mycorrhizal networks can connect several plants simultaneously, the transfer of resource across a shared fungal network can shift depending on these factors.…”
Section: Introductionmentioning
confidence: 99%